The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan - Minoura, Kazushige; Mound, Laurence A. (Zootaxa, 2019)
Currently 10 species are listed in the genus Ophthalmothrips: amyae and conocephalus from South Africa, pomeroyi from Tanzania, lesnei from Mozambique, breviceps and faurei from India, formosanus from Taiwan, longiceps and miscanthicola from East Asia, and yunnanensis from China. Here, conocephalus is newly recorded from Madagascar, faurei from China and Japan, lesnei from Kenya, pomeroyi from Zaire (Democratic Republic of Congo), and the first records of males of lesnei and pomeroyi are provided. A key to males and females of the 10 species is provided.